How commensal microbes shape the physiology of Drosophila melanogaster. - Grenier, T.; Leulier, F. (Current opinion in insect science, 2020)
The interactions between animals and their commensal microbes profoundly influence the host's physiology. In the last decade, Drosophila melanogaster has been extensively used as a model to study host-commensal microbes interactions. Here, we review the most recent advances in this field. We focus on studies that extend our understanding of the molecular mechanisms underlying the effects of commensal microbes on Drosophila's development and lifespan. We emphasize how commensal microbes influence nutrition and the intestinal epithelium homeostasis; how they elicit immune tolerance mechanisms and how these physiological processes are interconnected. Finally, we discuss the importance of diets and microbial strains and show how they can be confounding factors of microbe mediated host phenotypes.